Physiological responses of two co-existing oak species in years with contrasting climatic conditions - Szőllősi, Erzsébet (Acta Biologica Szegediensis, 2011)
In this study we investigated how the intra- and inter-annual fluctuations of weather conditions influenced the physiological traits of sessile oak (Quercus petraea (Matt) Liebl.) and turkey oak (Quercus cerris L.) at Síkfőkút LTER site, Hungary, which is considered to be a peripherial habitat for Quercetum petraeae-cerris forest community. Seasonal changes in pigment composition and chlorophyll fluorescence parameters of upper (sun) and lower (shade) leaves of mature trees were studied during two consecutive growing seasons (2007, 2008). During the growing season of 2007 higher annual mean temperature and summer heat waves were recorded as compared to 2008. Leaves of both tree species had smaller chlorophyll content and higher total carotenoid content and xanthophyll cycle pool in summer of 2007 than in 2008. Changes of latter leaf traits under stress conditions in summer of 2007 were indicative for appearance of photoinhibition under heat stress. In 2007 lower Fv/Fo values also reflected more severe heat-induced decrease in shade leaves of both species compared to 2008. Recovery of Fv/Fo took place after the hot days of 2007 only in leaves of turkey oak.